Comparative analysis of the bioaccumulation of bisphenol A in the blood serum and follicular fluid of women living in two areas with different environmental impacts - Raimondo, Salvatore; Chiusano, Maria Luisa; Gentile, Mariacira; Gentile, Tommaso; Cuomo, Felice; Gentile, Raffaella; Danza, Domenico; Siani, Laura; Crescenzo, Claudia; Palmieri, Mariangela; Iaccarino, Stefania; Iaccarino, Mirella; et al. (Frontiers in Endocrinology, 2024)
Background: Bisphenol A (BPA) is a common contaminant widely used in many industrial sectors. Because of its wide use and dispersion, it can be accumulated in human living bodies through both oral assumption and not-dietary routes. BPA exhibits hormone-like properties, falling in the class of endocrine disruptors, therefore it can alter relevant physiological functions. In particular, in women, it can affect folliculogenesis and therefore reproduction, contributing to infertility, but also to endometriosis and premature puberty. Methods: We conducted a multicenter study on 91 women undergoing a first In Vitro Fertilization (IVF) treatment cycle in the Campania region (Southern Italy). We investigated on the presence and concentration of BPA in serum and in follicle fluids to assess effects of airborn BPA contamination on these body fluids. The analysis was conducted recruiting on 32 women living in a Low Environmental Impact (LEI) area, from the Sele Valley River and Cilento region, and 59 women living in a High Environmental Impact (HEI) area, the so called "Land of Fires", a highly contaminated territory widely exposed to illegal waste practices. Results: A higher average BPA content in both blood serum and follicle fluid was revealed in the HEI group when compared with the LEI one. In addition, we revealed higher average BPA contents in the blood serum than in the follicle fluid from in the HEI area, with opposite average contents in the two fluids in the LEI zone. In addition, our results also showed a lack of correlation between BPA content in follicle and serum fluids both in the overall population, and in the HEI and in the LEI groups, with peculiar trends in different subsets of women.From our data results we can deduce revealed a heterogeneity in the diffusion distribution of BPA content between the serum and the follicular fluid.. Further studies are needed to support unraveling the bioaccumulation mechanisms of BPA in highly polluted and non-polluted areas.